2018
DOI: 10.1002/hsr2.90
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Ogata flow cytometric scoring system in routine diagnostics of myelodysplastic syndrome

Abstract: Background and AimsCompiling evidence has emerged for the relevance of flow cytometric assessment as a valuable part of the diagnostic work‐up of myelodysplastic syndrome (MDS). This study aimed at evaluating the implementation of a simple flow cytometric scoring system (FCSS), the Ogata score, in a routine diagnostic laboratory.MethodsA total of 35 patient samples with a clinical suspicion of MDS were retrospectively assessed using the FCSS. The accuracy of the FCSS was evaluated on the basis of the final dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…MFC will complement the primary morphological evaluation, especially in borderline cases where immunophenotypic aberrations can support or exclude MDS diagnosis (as illustrated in a diagnostic algorithm presented in Figure 1 in . The previous iMDSflow recommendation that the four-parameter Ogata score (Ogata et al, 2009) may be used for a preliminary assessment of MFC dysplasia has been confirmed by several publications (Bardet et al, 2015;Dhingra et al, 2020;Grille Montauban et al, 2019;Kárai et al, 2017;Mannelli et al, 2019;Matzen et al, 2018;Muyldermans et al, 2019;. This score is based on the frequency of myeloid CD34 + myeloid progenitors (MP) (>2%), the fraction of B-cell precursors within CD34 + cells (<5%), abnormal CD45 expression on CD34 + blasts, and low granulocyte scatter (granulocyte/lymphocyte SSC ratio ≤6).…”
Section: Minimal Requirements To Assess Dysplasia By Mfcmentioning
confidence: 97%
See 1 more Smart Citation
“…MFC will complement the primary morphological evaluation, especially in borderline cases where immunophenotypic aberrations can support or exclude MDS diagnosis (as illustrated in a diagnostic algorithm presented in Figure 1 in . The previous iMDSflow recommendation that the four-parameter Ogata score (Ogata et al, 2009) may be used for a preliminary assessment of MFC dysplasia has been confirmed by several publications (Bardet et al, 2015;Dhingra et al, 2020;Grille Montauban et al, 2019;Kárai et al, 2017;Mannelli et al, 2019;Matzen et al, 2018;Muyldermans et al, 2019;. This score is based on the frequency of myeloid CD34 + myeloid progenitors (MP) (>2%), the fraction of B-cell precursors within CD34 + cells (<5%), abnormal CD45 expression on CD34 + blasts, and low granulocyte scatter (granulocyte/lymphocyte SSC ratio ≤6).…”
Section: Minimal Requirements To Assess Dysplasia By Mfcmentioning
confidence: 97%
“…In the first publication, the frequency of B‐cell precursors was evaluated using gating based on forward vs. side scatter properties (Ogata et al, 2009 ). However, most laboratories nowadays include CD19 to increase precision (Guo et al, 2020 ; Matzen et al, 2018 ; Rajab & Porwit, 2015 ). The four parameters carry different weights in the evaluation of dysplasia.…”
Section: Minimal Requirements To Assess Dysplasia By Mfcmentioning
confidence: 99%
“…FACS Lysing Solution and a stain-lyse-wash protocol, which we used, significantly reduce the light scatter CV for the different leukocyte populations compared to ammonium chloride [ 31 ], and may therefore influence the granulocyte/lymphocyte SSC ratio. However, this staining procedure did not decrease the sensitivity of the Ogata score in our cohort, and Matzen et al also used FACS Lysing solution with high specificity in their MDS analysis [ 32 ], so the FACS Lysing solution is unlikely to have a significant effect on the SSC ratio. The specificity of the “3 aberrations in two cell compartments method” was found to be higher (79%), although this figure is still far from 100%.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, many other study groups have achieved similar diagnostic values. 15,16 Since the time when the Ogata score was published, numerous related scales have been created for the diagnosis of MDS, many of which assume the assessment of similar parameters. Karai et al extended this scale to include erythrocyte maturation cell lines by adding CD71 and mast cell percentage, achieving higher sensitivity (84%) for low-grade MDS.…”
Section: Cytometric Scales In the Diagnosis Of Myelodysplastic Syndromesmentioning
confidence: 99%